Pengaruh Kreativitas Belajar Dan Disiplin Belajar Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Pendidikan Kewarganegaraan di Kelas XI SMA Negeri 2 Pematang Siantar - Dika Ningsi Siregar; Wesly Nababan; Daulat Nathanael Banjarnahor (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2022)
This study aims to determine whether there is an influence of learning creativity and learning discipline on Students Achievement in Class XI SMA Negeri 2 Pematangsiantar for the Academic Year 2022/2023. The problem in this study is how the influence of learning creativity and learning discipline on student achievement in class XI SMA Negeri 2 Pematangsiantar 2022/2023. The population and sample in this study were class X as many as 26 people. To obtain data on learning creativity and learning discipline, researchers used a questionnaire as a data collection tool and used a closed questionnaire structured in a structured manner where the question items were followed by answers consisting of four choices. The quality of the research instrument for the questionnaire was assessed through validity and reliability tests. The next step is to test the hypothesis by calculating the linear regression equation, namely Y over X1 is = 83.60 + 0.06 X1 meaning that between the variables X1 is linear with Y and Y over X2 is = 74,37+(0.8) X2 means that between variables X2 is linear with Y and Y over X1 and X2 is = 1.33 + 0.53 X1 + 0.69 X2, meaning that between variables X1 and X2 is linear with Y.